Effectiveness of Mulligan Mobilization Versus Scapular Mobilisation technique on Functional Ability in Subjects with Adhesive Capsulitis of Shoulder Joint. - M. S., Sundar Rajan; Kotteeswaran K.; Hariharan J. (Indian Journal of Physiotherapy & Occupational Therapy)
Background and aim: Frozen shoulder or Adhesive capsulitis is determined by pain, progressive loss of active and passive shoulder range of motion due to the contracture of the joint capsule and fibrosis. The Mobilizations with movement (MWM) for joints are used separately or along with other hands-on techniques to increase the quality of joint intra articular gliding, neurodynamic and to assist the correct muscle demand. The goal of study is to assess the effectiveness of Mulligan 'MWM' and Scapular mobilization technique on functional ability in subjects with adhesive capsulitis of shoulder Methods: Total 40 subjects were selected based on the inclusion and exclusion criteria. The detailed procedure was explained to subjects, and Informed consent form was collected before starting the study. The Pre and Post test values were measured using ROM and Shoulder Pain and Disability Index. The subjects were divided into two groups: Mulligan 'MWM' with exercise: (n=20), Scapular mobilization technique with exercise: (n=20). Both groups received Arm Circles, Pendulum stretch, Towel stretch, Wand exercise, wall climbing, upper body stretch for 3 days a week and continued for 6 weeks (2 sets, 10 repetition with 10 seconds hold were given). Result: The collected data was statistically analyzed using an unpaired t-test. Mulligan 'MWM' indicates significant effects (p <0.01) in reducing pain and improving functional activity when compared to Scapular mobilization technique along with exercise, assessed by ROM and SPADI. Conclusion: This study concluded that mulligan 'MWM' is more effective than Scapular mobilization technique along with exercises reducing pain and improving functional activity in adhesive capsulitis of shoulder joint.